Siah regulation of Pard3A controls neuronal cell adhesion during germinal zone exit - Famulski, Jakub K. (2010)
The brain’s circuitry is established by directed migration and synaptogenesis of neurons during development. Although neurons mature and migrate in specific patterns, little is known about how neurons exit their germinal zone niche. We found that cerebellar granule neuron germinal zone exit is regulated by proteasomal degradation of Pard3A by the Seven in Absentia homolog (Siah) E3 ubiquitin ligase. Pard3A gain-of-function and Siah loss-of-function induce precocious radial migration. Time-lapse imaging using a probe to measure neuronal cell contact reveals that Pard3A promotes adhesive interactions needed for germinal zone exit by recruiting the JAM-C epithelial tight junction adhesion molecule to the neuronal cell surface. Our findings define a Siah-Pard3A signaling pathway that controls adhesion-dependent exit of neuronal progenitors or immature neurons from a germinal zone niche.